Knowledge integration mechanism as mediator between leadership styles and enterprise systems success - Ghazali, Razatulshima (2015)
Many organisations in developing countries invest huge amounts of capital in Enterprise Systems (ES), with the intention to gain all the benefits offered by such systems. Unfortunately, the failure rate of ES implementation in developing countries is high. According to a systematic literature review of research on ES critical success factors, 100 percent of these failures occur due to the lack of management or leadership support and commitment, particularly in the ES post-implementation phase. Many studies in the literature also report the power of Knowledge Management (KM) to assist organisational superiors in ES post-implementation phase. These studies highlight the capability of one of the most neglected KM processes, namely, Knowledge Integration (KI), and explore the crucial involvement of organisational superiors with different leadership styles (such as transformational and transactional) in the ES post-implementation phase through the employment of quantitative research methods. The present study commenced with an intensive literature review, and a series of interviews with company experts in order to identify the research gap and confirm the validity and reliability of the constructs in the developed survey. A total of 508 valid survey responses were analysed using the Partial Least Squares-Structural Equation Modelling (PLS-SEM) approach. Mediating effect tests were performed using bootstrapping procedures to test the role of KI mechanisms as a mediator. The results indicate that KI mechanisms fully mediate the relationship between transactional leadership style and ES success. Conversely, KI mechanisms partially mediate the relationship of transformational leadership style and ES success. The results expose the importance of the both leadership styles and superiors’ adoption of KI mechanisms when managing the ES in the post-implementation phase and highlighted the leadership practices and the mechanisms of KI that should be prioritised during the ES post-implementation phase.